Correlations of Scapular Dimensions: A Tool to Identify Scapulae with Completely Ossi􀂦ed Superior Transverse Scapular Ligaments and Suprascapular Neuropathy - Adewale, Adesanya Olamide; Segun, Okeniran Olatayo; Usman, Ibe Michael; Monima, Ann Lemuel; Kegoye, Eric Simidi; Kasozi, Keneth Iceland; Nalugo, Halima; Ssempijja, Fred (Research square, 2020)
Background. A better understanding of the anatomy of the suprascapular notch and relationship with scapular dimensions are vital in the diagnosis, prevention, and assessment of the suprascapular nerve (SN) entrapment syndrome. Our purposes were to classify the suprascapular notches, determine the prevalence of completely ossified superior transverse scapular ligament, scapular dimensions, and their relationship among the different types of the suprascapular notch (SSN). Methods: An experimental study in which the SSN types and scapular dimensions were determined using previous methods. Statistical analyses were done using GraphPad Prism v.6 and MS Excel Version 2019, one-way ANOVA was used to compare and Spearman’s correlation coefficient was used to evaluate the correlation of scapular dimensions. Results: The superior transverse scapular ligament (STSL) was completely ossified in 8% of cases. There were no significant differences between the scapular dimensions for the different SSN types. For type VI SSN there is a strong negative correlation between A, B against D. There are strong (positive or negative) correlations between types I and III from type VI for A-axis; types I, III from VI for B; type IV and VI for C axis; and type III and VI for D axis. Conclusions: The prevalence of the completely ossified STSL in our study was moderately high; the correlation studies suggest that the scapular dimensions could be a valuable tool in the prediction, diagnosis, prevention, and assessment of the SN neuropathy due to the scapulae with the completely ossified superior transverse scapular ligaments (type VI SSN). Further studies on correlation analyses of scapular dimensions and characteristics of suprascapular notches are vital.
Keywords: Suprascapular notch; Completely Ossified Superior Transverse Scapular Ligament; Scapular dimensions; Suprascapular nerve Entrapment Syndrome; Anatomical variation